dragon: Multidimensional range queries on distributed aggregation trees - Carlini, Emanuele; Lulli, Alessandro; Ricci, Laura (Future generation computer systems, 2016)
Distributed query processing is of paramount importance in next-generation distribution services, such as Internet of Things (IoT) and cyber–physical systems. Even if several multi-attribute range queries supports have been proposed for peer-to-peer systems, these solutions must be rethought to fully meet the requirements of new computational paradigms for IoT, like fog computing. This paper proposes dragon, an efficient support for distributed multi-dimensional range query processing targeting efficient query resolution on highly dynamic data. In dragon nodes at the edges of the network collect and publish multi-dimensional data. The nodes collectively manage an aggregation tree storing data digests which are then exploited, when resolving queries, to prune the sub-trees containing few or no relevant matches. Multi-attribute queries are managed by linearizing the attribute space through space filling curves. We extensively analysed different aggregation and query resolution strategies in a wide spectrum of experimental set-ups. We show that dragon manages efficiently fast changing data values. Further, we show that dragon resolves queries by contacting a lower number of nodes when compared to a similar approach in the state of the art. •We have defined and implemented a support for multidimensional range query in distributed systems.•We exploited space filling curves to support the multi dimensionality.•The proposal is based on the definition of a distributed aggregation tree.•We investigated several aggregation techniques.•The paper includes an extensive experimental analysis of the system and a comparison with a state of art proposal.